Kolaborasi TK ABA Bebekan dan Masyarakat dalam Mewujudkan Lingkungan Asri di Desa Bebekan, Taman Sidoarjo - Juniar, Nanda Devi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Issues related to cleanliness and environmental utilization around this educational institution are the main focus of this community service program. This initiative aims to describe and examine the relationship between ABA Bebekan Kindergarten and the residents of Bebekan Village, Taman District, Sidoarjo, in an effort to create a beautiful, clean, and comfortable environment that also functions as a means of character education for early childhood. The method applied is a descriptive qualitative approach and data collection techniques are carried out through observation, interviews, and documentation collection. The subjects of this activity include students, teachers, and the community around the school. The results of the activity indicate that collaboration through social activities, tree planting, utilization of empty spaces, and simple waste management can improve environmental conditions in schools and foster environmental awareness as well as attitudes of responsibility, discipline, and cooperation among students. Changes are seen in the improvement of the quality of the physical environment at school and the development of good behavior in students' daily lives. Therefore, collaboration between schools and communities is an effective approach to creating environmental character and sustainable early childhood education.